1996
DOI: 10.7589/0090-3558-32.4.619
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneous Cryptosporidiosis in Captive White-Tailed Deer (Odocoileus Virginianus)

Abstract: In August 1994, cryptosporidiosis was diagnosed in a diarrheic fawn from a captive white-tailed deer (Odocoileus virginianus) herd maintained for research purposes at The University of Georgia's Warnell School of Forest Resources in Athens, Georgia (USA). From June through August 1995, 11 captive female white-tailed deer were housed in individual barn stalls where they gave birth to 18 fawns. Feces collected at 2 or 3 day intervals from the 18 neonatal fawns for at least 21 days and from 11 adult females once … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
10
0

Year Published

1999
1999
2021
2021

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 3 publications
0
10
0
Order By: Relevance
“…Based on morphometric analysis, in the previous reports of infections in deer cryptosporidia were designated C. parvum (13,29). In addition, for one of the captive deer isolates, the SSU rRNA gene sequence was identical to the C. parvum genotype 2 sequence (GenBank accession number AF093494).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Based on morphometric analysis, in the previous reports of infections in deer cryptosporidia were designated C. parvum (13,29). In addition, for one of the captive deer isolates, the SSU rRNA gene sequence was identical to the C. parvum genotype 2 sequence (GenBank accession number AF093494).…”
Section: Discussionmentioning
confidence: 99%
“…Cryptosporidium infection was first reported in white-tailed deer in a captive herd in Georgia in a small sample of neonatal fawns and their mothers; most infections were asymptomatic (13). Recently, the first study of Cryptosporidium infection in wild white-tailed deer was described (29); the prevalence of infection was determined by microscopic methods.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…8,9,20,30 However, detection in older animals may be considered by some to be unusual. In cattle, natural infections with C. parvum have been reported in calves as young as 4 days but appeared to be most common around 2 weeks of age.…”
Section: Discussionmentioning
confidence: 99%
“…8 That study demonstrated that captive WTD can excrete C. parvum oocysts that are infectious for other mammals. However, the role of free-ranging WTD in the epidemiology of cryptosporidiosis could not be inferred from that study.…”
mentioning
confidence: 99%